Prognostic and Diagnostic Values of Semaphorin 5B and Its Correlation With Tumor-Infiltrating Immune Cells in Kidney Renal Clear-Cell Carcinoma - Ding, Junping; Zhao, Shubin; Chen, Xianhua; Luo, Changjun; Peng, Jinjian; Zhu, Jiantan; Shen, Yongqi; Luo, Zhou; Chen, Jianlin (Frontiers in Genetics, 2022)
Abstract Background: Semaphorin 5B(SEMA5B) has been described to be involved in the development and progression of cancer. However, the potential diagnostic, prognosis roles and its correlation with tumor-infiltrating immune cells in KIRC has not been clearly reported for the present. Methods: The mRNA level of SEMA5B was analyzed via TCGA, GTEx database as well as CCLE dataset and verified by GSE53757, GSE40435 datasets. Meanwhile, the protein level of SEMA5B was analyzed by CPTAC and validated by HPA. The diagnostic value of SEMA5B was analyzed according TCGA database and validated by GSE53757, GSE46699, and GSE11024+GSE46699 datasets. Then, the survival analysis was conducted using GEPIA2. R software (v3.6.3) was applied to investigate the relevance between SEMA5B and immune checkpoints and m6A RNA methylation regulators expression. The correlation between SEMA5B and MMRs and DNMTs expression and tumor-infiltrating immune cells were explored via TIMER2. Coexpressed genes of SEMA5B were assessed by cBioPortal and enrichment analysis was conducted by Metascape. The methylation analysis was conducted with MEXPRESS and MethSurv online tools. Gene set enrichment analysis (GSEA) was applied to annotate the biological function of SEMA5B. Results: SEMA5B was significantly upregulated at both the mRNA and protein levels in KIRC. Further analysis demonstrated that mRNA expression of SEMA5B were significantly correlated with gender, age, T stage, pathologic stage, and histologic grade. High levels of SEMA5B were found to be a favorable prognostic factor and novel diagnostic biomarker for KIRC. SEMA5B expression was shown to be significantly associated with the abundance of immune cells in KIRC. And SEMA5B expression was significantly correlated with the abundance MMR genes, DNMTs and m6A regulators in KIRC. Enrichment analysis indicated that the coexpressed genes may involve in the crosslinking in extracellular matrix (ECM). GSEA disclosed that SYSTEMIC_LUPUS_ERYTHEMATOSUS and NABA_ECM_REGULATORS were prominently enriched in SEMA5B low expression phenotype. Finally, the methylation analysis demonstrated a correlation between hypermethylation of the SEMA5B gene and a poor prognosis in KIRC. Conclusions: Increased SEMA5B expression correlates with immune cell infiltration, which can be served as a favorable prognostic factor and a novel diagnostic biomarker for KIRC.